Modern imaging modalities in forensic anthropology and the potential of low-dose X-rays. (December 2020) - Mamabolo, B.; Alblas, A.; Brits, D.
Highlights: Low-dose X-rays produce high resolution, full-body 2D images in less than 13 seconds. Low-dose X-rays is user-friendly and requires little training to operate. Low-dose X-rays accurately detects skeletal fractures. Lose dose X-rays show negligible measurement error in the scanning axis which allow for accurate data collection. Abstract: The use of imaging modalities is becoming increasingly popular in forensic anthropology. Imaging modalities that have been used in forensic anthropology to date include; surface scanning, photogrammetry, sonography, Computed Tomography (CT), Magnetic Resonance Imaging (MRI) and conventional X-rays. Little is however, known about low-dose X-rays and its potential use in forensic anthropology. The aim of this review article is to briefly introduce the imaging modalities that have been used in forensic anthropology, by introducing their advantages and disadvantages, as well as highlighting its specific use in forensic anthropology, with emphasis on low-dose Xrays. Low-dose X-ray produces high resolution, full-body 2D images, without the need for image stitching, in less than 13 seconds. It is a user-friendly system that requires minimal training to operate and the setup thereof is cheaper than other imaging modalities. It was also found that low-dose X-rays often outperformed other imaging modalities. The use of low-dose X-ray in forensic anthropology is still in its infancy and as it is more frequently available and easily accessible in medico-legal laboratories, its full potential should be further explored.